2005
DOI: 10.1093/hmg/ddi068
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel adult-onset primary open-angle glaucoma (POAG) gene on 5q22.1

Abstract: Glaucoma is a leading cause of blindness in virtually every country. Development of an accurate diagnostic test for presymptomatic detection of individuals at risk is an urgent requisition for this condition. Herein, we report mapping of a new adult-onset primary open-angle glaucoma (POAG) locus on 5q22.1 (GLC1G) and identification of its defective gene. Mutation screening of seven candidate genes from the GLC1G critical region (approximately 2 Mb between D5S1466 and D5S2051) identified only one significant al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
245
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(258 citation statements)
references
References 23 publications
5
245
0
2
Order By: Relevance
“…55,56 Moreover, it has been shown that the size of the anterior chamber is strongly determined by genetic components, suggesting that morphological characteristics predisposing to PACG are also heritable. 52,53 Recent advances have indicated several genes and genetic loci [57][58][59][60] that may be causative for POAG, but evidence for genes causing PACG remains sparse. The first evidence for a genetic locus linked to familial PACG comes from the analysis of a large family with nanophthalmos, hyperopia, and angle closure glaucoma.…”
Section: Pacg Risk Factorsmentioning
confidence: 99%
“…55,56 Moreover, it has been shown that the size of the anterior chamber is strongly determined by genetic components, suggesting that morphological characteristics predisposing to PACG are also heritable. 52,53 Recent advances have indicated several genes and genetic loci [57][58][59][60] that may be causative for POAG, but evidence for genes causing PACG remains sparse. The first evidence for a genetic locus linked to familial PACG comes from the analysis of a large family with nanophthalmos, hyperopia, and angle closure glaucoma.…”
Section: Pacg Risk Factorsmentioning
confidence: 99%
“…Only three genes causing POAG, MYOC, optineurin (OPTN), and WDR36, have been identified in these loci, that is, in GLC1A, GLC1E, and GLC1G, respectively. 9,13,46 Rare mutations associated with POAG in a novel gene, neurotrophin-4 (NTF4), have been recently identified in a European, as well as in a Chinese population. 47,48 A review of the literature on glaucoma genetics suggests a useful separation of them into those which are well-established glaucoma-causing genes, controversial genes that do not have an established role in glaucoma pathogenicity at present, and low-penetrance risk alleles that contribute to the likelihood of getting disease, but don't cause disease on their own.…”
Section: Genetic Loci and Glaucoma-associated Genesmentioning
confidence: 99%
“…Monemi et al 46 observed that one of the four identified disease-causing mutations of WDR36, D658G, maps to the C-terminal part of the cytochrome heme cd1 domain, which is part of an enzyme with cytochrome oxidase activity. A gene responsible for primary congenital glaucoma, cytochrome P450, subfamily 1, polypeptide 1 (CYP1B1), is also a member of the cytochrome P450 family.…”
Section: Wdr36 At the Glc1g Locusmentioning
confidence: 99%
“…7 However, only three causative genes have been described so far, including: myocilin (MYOC/GLC1A), 8 optineurin (OPTN/GLC1E) 9 and WD repeat domain 36 (WDR36/GLC1G). 10 Altogether, mutations in these genes account for o10% of POAG cases. 11 In addition, association studies have implicated at least 20 other genes, 7,12 among them cytochrome P450-1B (CYP1B1) 13 and neurotrophin 4 (NTF4), 14 contributing to the pathogenesis of glaucoma, 7 but these are still insufficient to explain the most significant fraction of POAG cases.…”
Section: Introductionmentioning
confidence: 99%